Teachers’ Knowledge and Challenges in Using Artificial Intelligence (AI)-Based Learning Media: An Educational Administration Perspective at MIN 3 Bandar Lampung - Arifani, Laksmi; Dacholfany, Muhammad Ihsan; Andayani, Sutrisni (Dirasah: Jurnal Pendidikan Islam, 2026)
This study aims to analyze teachers' knowledge, obstacles in utilization, and educational administrative support regarding the implementation of Artificial Intelligence (AI)-based learning media at MIN 3 Bandar Lampung. The study specifically involved 35 teachers at MIN 3 Bandar Lampung, with 10 teachers selected as the main informants through purposive sampling based on their involvement and experience in the learning process and the use of digital learning media. The study employed a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation. The results indicate that teachers’ understanding of AI is still limited to general technological introduction, without sufficient understanding of adaptive functions and learning personalization as the main characteristics of Artificial Intelligence (AI). Although several teachers have utilized AI-based platforms such as Quizizz, Canva, and Google Forms, they were not fully aware of the AI elements embedded within these platforms. The implementation of Artificial Intelligence (AI) is also constrained by limited infrastructure, low digital literacy, lack of training, administrative burdens, and the absence of institutional policies supporting AI integration. Schools have mainly provided moral support without systematic policies or continuous training programs.  This study concludes that the utilization of Artificial Intelligence (AI) at MIN 3 Bandar Lampung remains at an early stage. Therefore, strengthening AI literacy, improving infrastructure, providing continuous training, and establishing targeted institutional policies are necessary to support effective learning transformation.